ART-TEXT: AN UNUSUAL DIVING IN PICTURES, CONCEPTS AND EXPERIENCES - Riani Costa, Camilo Floriano; Pereira Leite, Cesar Donizetti [UNESP] (Univ Estadual Campinas, Fac Educacao, 2018)
Art has occupied a growing space in the most distinct discussions about the constitution of the subject, whether by the bias of experience, whether by the subjectivity, among many others. Amidst a scenario lined with the power of countless escape routes, would there be a possible route to say of art, art, art, art? From the reflections and dives of the art-thesis 'Caricats: art-face-humor-experience', as well as initiatives from the Imago group (Unesp / Rio Claro), in dialogue with Deleuze, Guatarri, Foucault and others, an art-article composed entirely of visual compositions, which takes us to a space where art, humor and experience come to weave new nuances, new textures, new questions ...
Keywords: Art; Visual; Humor; Experience; Subjectivity